1982
DOI: 10.1007/bf01976423
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of cork barrier formation as a resistance mechanism to berry disease (Colletotrichum coffeanum) in arabica coffee

Abstract: The histology of resistance to coffee berry disease (CBD) was studied in artificially inoculated berries and hypocotyls of 6-week old seedlings of a number of varieties of Coffea arabica L. In resistant varieties a phellogen was quickly formed some cell layers below the site of infection and progress of the fungal invasion was effectively blocked by a complete barrier of suberized cells. Such barriers were absent or incompletely developed in CBD susceptible varieties. A highly significant correlation (r = 0.87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Masaba and Helderman (1985) also found that hypocotyls of Rume Sudan and SL 28 formed compounds that inhibited the conidia germination and the mycelial growth of C. kahawae, 2 days after the inoculation. According to Masaba and van der Vossen (1982), the resistance to CBD in Arabica coffee may, to a certain extent, be based on the formation of cork barriers. Phellogen was rapidly formed in some cells below the infection site and the progress of the fungal invasion was blocked by a complete barrier of suberised cells.…”
Section: Cytological and Biochemical Resistance Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Masaba and Helderman (1985) also found that hypocotyls of Rume Sudan and SL 28 formed compounds that inhibited the conidia germination and the mycelial growth of C. kahawae, 2 days after the inoculation. According to Masaba and van der Vossen (1982), the resistance to CBD in Arabica coffee may, to a certain extent, be based on the formation of cork barriers. Phellogen was rapidly formed in some cells below the infection site and the progress of the fungal invasion was blocked by a complete barrier of suberised cells.…”
Section: Cytological and Biochemical Resistance Mechanismsmentioning
confidence: 99%
“…These cork barriers corresponded macroscopically to the scab lesion, the common macroscopic expression of resistance to CBD (Gichuru, 1997). Such a resistance mechanism is likely to be stable (race-nonspecific) and depends apparently on actively metabolizing plant tissues (Masaba and van der Vossen, 1982;Masaba and Waller, 1992). In fact, cork barrier formation was observed in both attached berries and hypocotyls but not in detached berries, which quickly lost their ability to respond to C. kahawae infection.…”
Section: Cytological and Biochemical Resistance Mechanismsmentioning
confidence: 99%
“…Instead, host resistance appears to be largely based on the rapid formation of a cork barrier in the pericarp of the developing fruit or cortex of hypocotyl stems distal from the initial infection site, which eVectively prevents the pathogen from further invading healthy tissue (Masaba and Van der Vossen 1982). Such barriers are usually absent or incomplete in susceptible host plants.…”
Section: Resultsmentioning
confidence: 97%
“…Like most Colletotrichum species (Bailey et al 1992), C. kahawae is a hemibiotrophic pathogen with a two-phase infection process, one short biotrophic (Chen et al 2004) followed by a destructive necrotrophic phase in susceptible host plants (Masaba and Van der Vossen 1982). Early response to infection in resistant hosts was observed to include rapid cell death (Anon 2005), but it is not necessarily similar to the hypersensitive response, which is so characteristic of biotrophic pathogens such as coVee leaf rust (Hemileia vastatrix).…”
Section: Resultsmentioning
confidence: 99%
“…Baayen, manuscript in preparation) and intended for localization of pathogens. Similar situations occur in Botrytis cinerea ghost spots of tomato fruits (De Leeuw, 1985) and in coffee resistant to coffee berry disease (Masaba and Van der Vossen, 1982).…”
Section: Discussionmentioning
confidence: 91%